Perancangan Ui/Ux Kuliner Smart Fisheries Village Bangsring Menggunakan User Centered Design - Maulana, Hizbi; Hadiq, H (LPPM STIKOM Tunas Bangsa, 2024)
Smart Fisheries Village Bangsring (SFV) is a concept for fishing villages that integrates advanced technology to advance the fisheries and tourism sectors. In this context, designing the user interface (UI) and user experience (UX) for culinary applications in SFV becomes crucial in ensuring success and acceptance by the public and tourists. In facing this development, the problem that arises is the lack of a system that effectively integrates information about local culinary delights, causing a lack of awareness and accessibility for visitors and local communities to the existing culinary riches. This research aims to design the culinary UI/UX of the SFV web-based application using a User Centered Design (UCD) approach to ensure the suitability of the application to user needs and preferences. The UCD method is used in the stages of user needs analysis, concept design, prototype development, and evaluation through user interviews and usability testing. The results of this research include user-friendly interface design, intuitive navigation, and satisfactory user experience. It is hoped that by implementing the UCD approach, culinary applications in (SFV) can increase user involvement and contribute to the development of tourism and the local economy. In conclusion, designing culinary UI/UX using UCD is an effective strategy in creating applications that are responsive to user needs in smart village environments such as (SFV). The average SUS score is 98 which is in the excellent category. With these results it can be concluded that the information system created has succeeded in providing the information needed by users and has resolved the problems experienced by users.